Dynamic lung behavior under high G acceleration monitored with electrical impedance tomography. (27th September 2021) - Menden, Tobias; Alcaín, Gema B; Stevenson, Alec T; Pollock, Ross D; Tank, Henry; Hodkinson, Peter; Jolley, Caroline; Smith, Thomas G; Leonhardt, Steffen; Walter, Marian
Abstract: Objective . During launch and atmospheric re-entry in suborbital space flights, astronauts are exposed to high G-acceleration. These acceleration levels influence gas exchange inside the lung and can potentially lead to hypoxaemia. The distribution of air inside the lung can be monitored by electrical impedance tomography. This imaging technique might reveal how high gravitational forces affect the dynamic behavior of ventilation and impair gas exchange resulting in hypoxaemia. Approach . We performed a trial in a long-arm centrifuge with ten participants lying supine while being exposed to +2, +4 and +6 G x (chest-to-back acceleration) to study the magnitude of accelerations experienced during suborbital spaceflight. Main results . First, the tomographic images revealed that the dorsal region of the lung emptied faster than the ventral region. Second, the ventilated area shifted from dorsal to ventral. Consequently, alveolar pressure in the dorsal area reached the pressure of the upper airways before the ventral area emptied completely. Finally, the upper airways collapsed and the end-expiratory volume increased. This resulted in ventral gas trapping with restricted gas exchange. Significance . At +4 G x, changes in ventilation distribution varied considerably between subjects, potentially due to variation in individual physical conditions. However, at +6 G x all participants were affected similarly and the influence of high gravitational conditions was pronounced.